2020
DOI: 10.1007/s10854-020-04428-x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning thermoelectric properties of Ca0.9Gd0.1MnO3 by laser processing

Abstract: Donor-doped CaMnO 3 is an n-type semiconductor with perovskite structure, being considered as a potential n-type leg in thermoelectric modules. This oxide presents stability at high temperatures and allows tuning the relevant electrical and thermal transport properties through doping. In this work, Ca 0.9 Gd 0.1 MnO 3 precursors have been prepared to produce fibres through the laser floating zone technique using different pulling rates. However, as-grown fibres did not present thermoelectric properties due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…rough the comparative analysis of the graph neural network cultured on the microfluidic array chip and the graph neural network cultured on the glass slide, the influence of the neural network on the neuron morphology was studied [5]. Ferreira N M prepared MnO 3 precursors to produce fibers by using the laser floating zone technique [6]. Guangyi proposed a novel water-vapor shrinkage-guided high-power laser processing (WSLP) technique.…”
Section: Introductionmentioning
confidence: 99%
“…rough the comparative analysis of the graph neural network cultured on the microfluidic array chip and the graph neural network cultured on the glass slide, the influence of the neural network on the neuron morphology was studied [5]. Ferreira N M prepared MnO 3 precursors to produce fibers by using the laser floating zone technique [6]. Guangyi proposed a novel water-vapor shrinkage-guided high-power laser processing (WSLP) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of synthesis of CMO-based ceramics reported that different thermoelectrical properties resulted when distinct synthesis methods were adopted and concluded that a chemical route enabled higher ZT values than the statesolid reaction method [15]. Also, the presence of secondary phases affects the electrical conductivity compared to the stoichiometric CMO [16].…”
Section: Introductionmentioning
confidence: 99%